Effectiveness–implementation hybrid-2 randomised trial of a collaborative Shared Care Model for Detecting Neurodevelopmental Impairments after Critical Illness in Young Children (DAISY): pilot study protocol. Issue 7 (15th July 2022) - Long, Debbie; Gibbons, Kristen; Dow, Belinda; Best, James; Webb, Kerri-Lyn; Liley, Helen G; Stocker, Christian; Thoms, Debra; Schlapbach, Luregn J; Wharton, Carolyn; Lister, Paula; Matuschka, Lori; et al.
Abstract : Introduction: In Australia, while paediatric intensive care unit (PICU) mortality has dropped to 2.2%, one in three survivors experience long-term neurodevelopmental impairment, limiting their life-course opportunities. Unlike other high-risk paediatric populations, standardised routine neurodevelopmental follow-up of PICU survivors is rare, and there is limited knowledge regarding the best methods. The present study intends to pilot a combined multidisciplinary, online screening platform and general practitioner (GP) shared care neurodevelopmental follow-up model to determine feasibility of a larger, future study. We will also assess the difference between neurodevelopmental vulnerability and parental stress in two intervention groups and the impact of child, parent, sociodemographic and illness/treatment risk factors on child and parent outcomes. Methods and analysis: Single-centre randomised effectiveness–implementation (hybrid-2 design) pilot trial for parents of children aged ≥2 months and <4 years discharged from PICU after critical illness or injury. One intervention group will receive 6 months of collaborative shared care follow-up with GPs (supported by online outcome monitoring), and the other will be offered self-directed screening and education about post-intensive care syndrome and child development. Participants will be followed up at 1, 3 and 6 months post-PICU discharge. The primary outcome is feasibility. Secondary outcomes include neurodevelopmental vulnerability and parental stress. An implementation evaluation will analyse barriers to and facilitators of the intervention. Ethics and dissemination: The study is expected to lead to a full trial, which will provide much-needed guidance about the clinical effectiveness and implementation of follow-up models of care for children after critical illness or injury. The Children's Health Queensland Human Research Ethics Committee approved this study. Dissemination of the outcomes of the study is expected via publication in a peer-reviewed journal, presentation at relevant conferences, and via social media, podcast presentations and open-access medical education resources. Registration details: The trial was prospectively registered with the Australian New Zealand Clinical Trials Registry as 'Pilot testing of a collaborative Shared Care Model for Detecting Neurodevelopmental Impairments after Critical Illness in Young Children' (the DAISY Pilot Study). Trial registration number: ACTRN12621000799853.